The effects of social participation on social integration - Xie, Peng; Cao, Qinwei; Li, Xue; Yang, Yurong; Yu, Lianchao (Frontiers in Psychology, 2022)
With the fast expansion of urbanization, temporary migrants have become a large demographic in Chinese cities. Therefore, in order to enhance the social integration of the migrant population, scholars and policymakers have an urgency to investigate the influencing factors of the integration progress. Prior studies regarding social integration have neglected to examine this topic from the perspective of social participation. Empirical research is conducted based on the data of 15997 migrants across eight cities in the 2014 wave of National Migrant Population Dynamic Monitoring Survey (MDMS) in China. Hierarchical linear models were used to test the hypotheses regarding the impacts of formal and informal social participation on social integration. Community type, neighbor composition, hometown pressure, withdrawal guarantee, and constraints of hukou were examined as moderators. Formal and informal social participation possess different features such as operating with distinct modes, providing different services. Members within the organizations also entail different rights and responsibilities, providing them with different types of social capital and psychological perceptions. Hence, this study strived to identify the effects of social participation behaviors on social integration from a social capital perspective. The results revealed that social participation is positively linked to social integration. We also distinguished between formal and informal social participation of migrants to investigate the boundary effects of different types of social participation on social integration. The findings provide both theoretical and practical implications for scholars as well as policymakers on issues regarding the social integration of migrants.